The case for a new reformation theology - Hordern, William (Philadelphia : Westminster Press, 1959)
Re-examination of the position of the Reformers and its relevance for twentieth century man, by an exponent of neo-orthodox theology.
Challenge and response in twentieth-century theology -- Faith and reason -- The nature of revelation -- How can we know that revelation is revelation? -- God's immanence and transcendence -- Sin -- Salvation.
Bibliography: p. 172-173.
Keywords: Neo-orthodoxy.